Subcutaneous phaeohyphomycosis caused by Alternaria section Alternaria - Xiujiao Xia; Zehu Liu; Hong Shen (International Journal of Infectious Diseases, 2023)
A woman presented with purulent infiltrating plaques on her hands and arms after a 7-year history of nephrotic syndrome. She was ultimately diagnosed with subcutaneous phaeohyphomycosis, which is caused by Alternaria section Alternaria. The lesions completely resolved after 2 months of antifungal treatment. Interestingly, spores (round-shaped cells) and hyphae were observed in the biopsy and pus specimens, respectively. This case report highlights that distinguishing subcutaneous phaeohyphomycosis from chromoblastomycosis may be difficult if the diagnosis is solely based on pathological findings. It also emphasizes that the parasitic forms of the dematiaceous fungi in immunosuppressed hosts may vary with the site and environment.